O virtuosismo nos escritos sobre música de Mário de Andrade: um olhar discursivo - Soares, Albergio Claudino Diniz (2014)
Taking into account the most diverse discourses about musical practices in Western civilization, it can be seen that what was built up around the phenomenon of virtuosity was significantly present at several moments in the history of this art. The discourses for, and even those against, the presence of virtuosity in music show that, besides being real, this presence has the power to shape the society in which it operates. This research rests its theoretical and analytical basis on the French concepts of Discourse Analysis, through the categories developed by Michel Foucault in many studies conducted throughout his investigative journey of the human sciences, such as: power-knowledge, truth-power, resistance and strategy. These sets of concepts allowed us to understand how the issue of virtuosity in music constituted a subject of discourse in Mário de Andrade s speeches and writings about music, materialized in his "Complete Works". This research made it possible to observe that Mario de Andrade s discursivity about virtuosity in music had a relationship with his militancy in Brazilian nationalist and modernist movements. At the same time, his discourse turned to be one of the elements of resistance to the European music practice prevailing in Brazilian scenery as well as a struggle strategy to build up a musical culture of genuinely Brazilian national character.